Kalkulacija stroškov za določanje prodajnih cen in odnosa s kupci - Hočevar, Marko (Les (Ljubljana), 2002)
In the recent years, with big changes in the environment of business, the meaning of (management) accounting information for management decisions, has increased. Contemporary management (cost) accounting systems must be designed to support decisions also about pricing and customer profitability. In this article cost calculation for short-term and long-term pricing and contemporary analyzing customer profitability are studied.
Keywords: analiza stroškov; cene; računovodstvo; poslovno odločanje